BIOCLIMATIC ADAPTATION OF TYPICAL HOUSES IN KAMPONG’S SURABAYA - Failasuf Herman Hendra; Antariksa Antariksa; Agung Murti Nugroho; Amin Setyo Leksono (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2018)
Architecture of an ancient house in Kampong’s Surabaya is one of the folk architecture creations in urban areas that grow and follow dynamics of urban development. In some of the city areas, this architecture is still sustainable for living space of city residents, especially for lower and middle class. Kampong as city villages has a high adaptability to development within the city so that it can adjust to future conditions efficiently. Cultures living in kampong require an appropriate strategy in associating with various limitations. However, limitation does not make a typical house in kampong uncomfortable and unlivable. Bioclimatic adaptation can be one of the strategies in development of typical ancient houses in kampong. It seems that typical ancient house in Surabaya City is influenced by tradition and style of Javanese, Colonial and Modern Architecture. Bioclimatic strategy is a design approach that considers the relationship of architecture to climate, biology, technology, in order to obtain comfort and energy efficiency. The form and performance of ancient house architecture in Surabaya City with a bioclimatic approach with occupant spatial interaction is an interesting topic for this study. This study is a descriptive research that using field studies. A method of description to explain the interaction between the building and its occupant that creates architecture of residential houses and its transformation.Bioclimatic adaptation as a design strategy allows a unique form architecture, climate responsive and environmentally friendly. Facade engineering and building envelopes, eco-friendly building materials, vegetation and water elements, saving energy with smart technologies.